Posterior spinal decompression in adults with spinal cord injury without traumatic compromise of the spinal canal: what is the data? - Solou, Mary; Politis, Anastasios A.; Ydreos, Ιoannis; Papadopoulos, Evangelos K.; Banos, Stamatios; Savvanis, Georgios; Gavra, Maria M.; Boviatsis, Efstathios J.; Stavrinou, Lampis C. (Frontiers in Neurology, 2023)
Background: Spinal cord injury (SCI) can be caused by a variety of factors and its severity can range from a mild concussion to a complete severing of the spinal cord. Τreatment depends on the type and severity of injury, the patient's age and overall health. Reduction of dislocated or fractured vertebrae via closed manipulation or surgical procedures, fixation and removal of bony fragments and debris that compromise the spinal canal are indicated for decompression of the spinal cord and stabilization of the spine. However, when there is no obvious traumatic obstruction of spinal canal, the question arises as to whether laminectomy is needed to be performed to improve neurological outcome. Methods :A literature review covering all indexed studies published between 2013 and 2023 was performed using keywords to identify the patient group of interest (spinal cord injury, SCI, spinal cord trauma, cervical, thoracic, lumbar, thoracolumbar),central cord syndrome (CCS) and the interventions (laminectomy, laminoplasty, decompression, duroplasty). Results: This review includes6 observational studies investigating the outcome of posterior spinal decompression in patients suffering from spinal cord injury without traumatic spinal cord stenosis,. Most patients already had degenerative stenosis. From a total of 202, 151 patients (74.7%) improved neurologically by at least one grade at ASIA scale, after being treated with either laminectomy, laminoplasty, duroplasty or a combination of these techniques. Conclusion: Early decompression in SCI patients remains a reasonable practice option and can be performed safely, but no specific evidence supports the use of laminectomy alone. There is emerging evidence that intended durotomy followed by extended meningoplasty may improve the neurological outcome in patients suffering from SCI when meta-traumatic edema is apparent. However, the lack of high-quality evidence and results support the need for further research.